1H-NMR metabolomics profiling of zebra mussel (Dreissena polymorpha): A field-scale monitoring tool in ecotoxicological studies. (1st February 2021) - Hani, Younes Mohamed Ismail; Prud'Homme, Sophie Martine; Nuzillard, Jean-Marc; Bonnard, Isabelle; Robert, Christelle; Nott, Katherine; Ronkart, Sébastien; Dedourge-Geffard, Odile; Geffard, Alain
Abstract: Biomonitoring of aquatic environments requires new tools to characterize the effects of pollutants on living organisms. Zebra mussels ( Dreissena polymorpha ) from the same site in north-eastern France were caged for two months, upstream and downstream of three wastewater treatment plants (WWTPs) in the international watershed of the Meuse (Charleville-Mézières "CM" in France, Namur "Nam" and Charleroi "Cr" in Belgium). The aim was to test 1 H-NMR metabolomics for the assessment of water bodies' quality. The metabolomic approach was combined with a more "classical" one, i.e ., the measurement of a range of energy biomarkers: lactate dehydrogenase (LDH), lipase, acid phosphatase (ACP) and amylase activities, condition index (CI), total reserves, electron transport system (ETS) activity and cellular energy allocation (CEA). Five of the eight energy biomarkers were significantly impacted (LDH, ACP, lipase, total reserves and ETS), without a clear pattern between sites (Up and Down) and stations (CM, Nam and Cr). The metabolomic approach revealed variations among the three stations, and also between the upstream and downstream of Nam and CM WWTPs. A total of 28 known metabolites was detected, among which four (lactate, glycine, maltose and glutamate) explained the observed metabolome variations between sites and stations, in accordance with chemical exposure levels. Metabolome changes suggest that zebra mussel exposure to field contamination could alter their osmoregulation and anaerobic metabolism capacities. This study reveals that lactate is a potential biomarker of interest, and 1 H-NMR metabolomics can be an efficient approach to assess the health status of zebra mussels in the biomonitoring of aquatic environments. Graphical abstract: Image 1 Highlights: Zebra mussels were caged around 3 water treatment stations of the Meuse district. 1 H NMR metabolomic approach was used combined to some classical energy biomarkers. Four identified metabolites were impacted: lactate, glycine, maltose, glutamate. Results suggest impairment of anaerobic and osmoregulation process. This study demonstrates the relevance of 1 H NMR metabolomics in ecotoxicology. Abstract : Results of this study showed the interest of 1H-NMR metabolomics as an efficient approach in biomonitoring of aquatic environments, and lactate could be a potential biomarker.